Pola Komunikasi Organisasi Dalam Pelaksanaan Event Lomba Tingkat Nasional - Jisca Putri Sagara Hati; Detya Wiryany; Ridma Meltareza (Lembaga Pengembangan Kinerja Dosen, 2024)
CREATIN photography competition event: Creative Moment INABA Photography Contest is a national level competition held to provide a platform for students from various universities to create high quality images based on a specific theme. The main purpose of this event is to encourage creativity, appreciate the art of photography, and promote the potential of young photographers, especially among students. This research uses a qualitative case study method to understand the phenomenon in depth. The focus of the research is a national-level photography competition event held by INABA University with the theme